2006
DOI: 10.1158/0008-5472.can-06-0709
|View full text |Cite
|
Sign up to set email alerts
|

Antagonism of CXCR3 Inhibits Lung Metastasis in a Murine Model of Metastatic Breast Cancer

Abstract: Tumor cells aberrantly express chemokines and/or chemokine receptors, and some may promote tumor growth and metastasis. We examined the expression and function of chemokine receptor CXCR3 in a syngeneic murine model of metastatic breast cancer. By flow cytometry, CXCR3 was detected in all murine mammary tumor cell lines examined. All human breast cancer cell lines examined also expressed CXCR3, as did the immortalized but nontumorigenic MCF-10A cell line. Interaction of CXCR3 ligands, CXCL9, CXCL10, and CXCL11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
189
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(208 citation statements)
references
References 17 publications
11
189
0
1
Order By: Relevance
“…Moreover, CXCL10 has been shown to be one of the Ras targets, and overexpressed in many cases of colorectal cancer (Zhang et al, 1997). Notably, a small molecular antagonist of CXCR3 has been recently reported to inhibit lung metastasis of breast cancer in a murine model, although they did not examine the metastatic potential to LNs (Walser et al, 2006). Thus, our present results suggest that CXCR3 can be a novel therapeutic target to suppress LN metastasis of colon and other CXCR3-expressing cancer cells.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, CXCL10 has been shown to be one of the Ras targets, and overexpressed in many cases of colorectal cancer (Zhang et al, 1997). Notably, a small molecular antagonist of CXCR3 has been recently reported to inhibit lung metastasis of breast cancer in a murine model, although they did not examine the metastatic potential to LNs (Walser et al, 2006). Thus, our present results suggest that CXCR3 can be a novel therapeutic target to suppress LN metastasis of colon and other CXCR3-expressing cancer cells.…”
Section: Discussionmentioning
confidence: 62%
“…Notably, CXCL9, CXCL10 and CCL21 play additional roles in the tumor microenvironment. For example, CXCL9 and CXCL10 activate RhoA and Rac1, induce actin reorganization, and trigger migration and invasion of melanoma, malignant B-lymphocyte, and lung and breast cancers (Trentin et al, 1999;Robledo et al, 2001;Soejima and Rollins, 2001;Kawada et al, 2004;Walser et al, 2006). Here, we have demonstrated that CXCR3 plays a critical role in colon cancer cell metastasis to LNs by inducing diverse cellular effects such as cytoskeletal rearrangement, migration, invasion, MMP-2/9 expression and cell survival through activation of ERK1/2 and Akt/PKB pathways.…”
Section: Discussionmentioning
confidence: 75%
“…It is worth noting that systemic administration of a small molecular inhibitor of CXCR3, AMG487, inhibits lung metastasis of HT29 CRC cells and breast cancer cells in a mouse model. 8,14 In addition, CXCR4-knockdown clones also significantly decreased metastasis to LNs, liver and lungs 6 weeks after inoculation, although its effect on LN metastasis was less. However, 2 weeks after inoculation, CXCR4-knockdown clones disseminated to LNs, liver and lungs at a similar frequency to that of the control clones, which was consistent with a previous report that CXCR4 is required for outgrowth of CRC micrometastases.…”
Section: Discussionmentioning
confidence: 98%
“…[6][7][8][9][13][14][15] In CRC, it was reported that CXCR3 expression is upregulated in metastatic colon cancer cells, but not in their primary lesions, and that the CXCL10/CXCR3 axis…”
mentioning
confidence: 99%
See 1 more Smart Citation